Reminder And Femininity In The Arabic Language – A Through Study In The Arab Heritage - Fadhil Hrkane, Mousa Jaafar (Opción, 2019)
The linguistic sex is important because of its importance in linguistics, it was a source of interest of Arab scientists, they wrote books in an attempt to break the confusion in it, and clarify the purpose of speech, as this phenomenon is wide- spread in grammar, It is worth mentioning that many languages around the globe distinguish between masculine and feminine sexes linguists, as well as in Arabic, which is considered to remember the origin of strength and rigidity in what is considered femininity branch, and perhaps the reason of this hypothesis origin The branch of linguistic sex is due to things (577 AH): ((The idea of sex or feminization and remembrance has retained elements that are not made of mental reasoning; because of some religious factors and others are reviewed by traditions and gen- eral beliefs. )). If we interpret this statement, we find it clear in Arabic. The harsh Bedouin life that casts its burden upon the man in everything has made him at the forefront of the board and in the arena of war or the applicants. When he leaves, he is the only one to bow down. The woman is behind him in the convoy. Wars, from here the reminder was the original and feminine branch came upon it.